2008
DOI: 10.4049/jimmunol.180.1.188
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus-Infected Insect Cells Expressing Peptide-MHC Complexes Elicit Protective Antitumor Immunity

Abstract: Evaluation of T cell responses to tumor- and pathogen-derived peptides in preclinical models is necessary to define the characteristics of efficacious peptide vaccines. We show in this study that vaccination with insect cells infected with baculoviruses expressing MHC class I linked to tumor peptide mimotopes results in expansion of functional peptide-specific CD8+ T cells that protect mice from tumor challenge. Specific peptide mimotopes selected from peptide-MHC libraries encoded by baculoviruses can be test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 55 publications
1
52
0
1
Order By: Relevance
“…To determine how particular peptide variants generate effective T-cell responses, we have used the CT26 transplantable colon tumor model (11,13,26). The immunodominant antigen of CT26, gp70 423-431 (AH1), is derived from a self-antigen encoded by the genome of BALB/c mice (27).…”
mentioning
confidence: 99%
“…To determine how particular peptide variants generate effective T-cell responses, we have used the CT26 transplantable colon tumor model (11,13,26). The immunodominant antigen of CT26, gp70 423-431 (AH1), is derived from a self-antigen encoded by the genome of BALB/c mice (27).…”
mentioning
confidence: 99%
“…The wild-type baculovirus-induced activation of host immunity and the inhibition of tumor growth are shown in Figure 1b; 20,21 however, mice treated with wild-type baculovirus also exhibited increased levels of serum ALT, AST and creatinine. We further investigated whether ALT, AST and creatinine increased in response to the administration of BVDCs.…”
Section: Levels Of Alt Ast and Creatinine Were Not Increased In Bv-dmentioning
confidence: 98%
“…Jordan et al demonstrated that vaccination with insect cells infected with recombinant, baculovirus-encoding peptide-MHC complexes generated peptide-specific cytotoxic T-cell responses and antitumor immunity. 20 We have previously described the induction of antitumor effects using wild-type baculovirus in a mouse model of hepatoma. 21 In particular, DCs were more potently infected by baculovirus than were other immune cells, and the DCs underwent activation and maturation.…”
Section: Introductionmentioning
confidence: 99%
“…For vaccination assays, 10 6 irradiated CT26-GM or CT26-βgal-GM cells were injected subcutaneously 16 or 14 and 7 days prior ex vivo examination or stimulation of splenocytes in culture as described [30]. Mice boosted with peptide received 5x10 6 Sf9 cells infected with recombinant baculovirus encoding peptide/H-2L d [34].…”
Section: Tumor Growth Assay Tumor Protection Assay and Peptide Vaccmentioning
confidence: 99%
“…51 Cr-labeled MC57G-Ld cells were incubated with the AH1 or MCMV pp89 peptide (YPHFMPTNL). In vivo killing assays were performed as described [34]. Briefly, splenocytes were loaded with the AH1 (CFSE-high) or βgal (CFSE-low, TPHPARIGL) peptide and injected intravenously into vaccinated mice.…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%